The Role of the Sumber Nyolo Sacred Natural Site in Plant Conservation and Ecosystem Services Based on Local Wisdom (A Case Study of Sumber Nyolo, Ngenep Village, Karang Ploso, Malang ) - Purnomo, Purnomo; Siregar, Aslam Chitami Priawan; Inaku, Awaluddin Hidayat Ramli; Saputra, Syifa (Berkala Ilmiah Biologi, 2025)
Abstract: The Sumber Nyolo Natural Sacred Site (NSS) is an area venerated by the local community and characterized by a distinctive plant community structure resembling a forest landscape. This study aims to analyze the role of the Sacred Natural Site (SNS) in plant conservation and ecosystem services, as well as to examine the cultural values of the local community associated with its existence. The research employed a plot sampling method, consisting of four plots distributed throughout the area, with plot sizes of 20 × 20 m for tree-level vegetation, 10 × 10 m for poles, 5 × 5 m for saplings, and 2 × 2 m for seedlings. Data were analyzed descriptively using the Importance Value Index (IVI), Shannon–Wiener diversity index (H’), Evenness index (E), Simpson’s dominance index (C), and endemism (End). A total of 53 plant species belonging to 26 families were recorded in the NSS. At the tree and sapling levels, Syzygium pycnanthum was the dominant species with the highest IVI values. At the pole level, co-dominance occurred among Bambusa blumeana, Dendrocalamus asper, and Syzygium littorale, while Syzygium littorale was dominant at the seedling level with the highest IVI value compared to other species. The plant community in the NSS is categorized as stable, as indicated by H’ values of 3.43 (trees), 3.17 (poles), 4.45 (saplings), and 2.23 (seedlings). Species distribution was relatively even, with E’ values of 0.60 (trees), 0.49 (poles), 0.74 (saplings), and 0.34 (seedlings). Moreover, the absence of a dominant species was indicated by C values approaching zero. Most of the recorded plants were local species with a high endemism rate of 94%. Vegetation in the NSS provides various ecological services, including regulating, provisioning, and supporting services. In addition, the NSS functions as a socio-cultural center for the local community, serving as the venue for traditional events such as the Bersih Desa ceremony.